Infant mortality as an indicator of inequality in the Chilean health system - Morales, Andrea (Journal Studies of Public Policy, 2016)
This work seeks to document the distribution of Infant Mortality Rate (IMR) at the community level and its causal relationship to socio-economic, demographic and health system factors. Vital statistics available from the Department of Health Statistics and Information (DEIS) and community features available on the National Municipal Information System (SINIM) were used from 2001 to 2011, for all of the 345 chilean comunes. Inequality indicators for infant mortality and income per capita in municipal health were built for each year and their correlation and evolution were evaluated during the period. The correlations of infant mortality rate to socioeconomic characteristics, health and municipal resources were evaluated using panel data models. The results show that while the national median of TMI by municipalities has been stable, inequality at the community level in this indicator has increased. The main communal features that generate higher infant mortality in different models tested, with confidence level of 95%, are higher rates of poverty, lower educational level of the population, no Primary Care Services of Emergency, poor municipal investment in health and greater distance from the base reference hospital.